Mesocellular silica foam supported polyamine adsorbents for dry CO2 scrubbing: Performance of single versus blended polyamines for impregnation. (1st December 2019) - Liu, Xin; Zhou, Kaixuan; Farndon, Matthew; Meier, Edward; Stevens, Lee; Liu, Hao; Sun, Chenggong
Highlights: Mesoporous silica supported polyamine adsorbents for CO2 capture were developed. Blended polyamine sorbents showed much higher CO2 capacities and faster kinetics. Blended amines showed higher thermal stability, due to suppressed urea formation. Abstract: Siliceous foams with three-dimensional mesoporous structures were synthesised and used to prepare polyethyleneimine (PEI) and tetraethylenepentamine (TEPA)-functionalised sorbent materials for CO2 capture, with a particular focus on the performance of impregnated amine blends versus single amine sorbent systems. Using thermal gravimetric analysis supported by other characterisations, the obtained results demonstrated that compared to the impregnated mono-component PEI and TEPA sorbent systems, the binary PEI-TEPA blend sorbents all achieved significantly higher CO2 capacities and faster adsorption kinetics, due to the enhanced formation of micro-cavities within the supported amine layers that led to reduced CO2 diffusion resistance and increased accessibility of the amines to CO2 . It was found that at 70 °C and 15% CO2 in N2, the CO2 adsorption capacity of the silica-supported PEI–TEPA (3:2) at 70 wt% amine loading increased by 40% compared to the supported PEI at the same level of amine impregnation, whilst the time to achieve 80% and 90% of the equilibrium adsorption capacity was reduced by 70% and 35%, respectively. Extended cyclic adsorption-desorption tests showed that the TEPA-blended PEI sorbents all exhibited considerably higher thermal stability than both the supported PEI and TEPA sorbents, being indicative of the suppressed urea formation even in the pure and dry CO2 gas stream used in the desorption cycles. Calculations indicated that compared to the silica-supported PEI sorbents, the higher adsorption capacities achieved by the binary PEI-TEPA sorbent systems could lead up to 10% reduction in the energy requirement for sorbent regeneration, highlighting the suitability of using amine blending as a facile effective strategy to promote the overall performance of polyamine-based adsorbents for CO2 separation.